Stabilization of switched linear systems with time-delay - Wang, M.; Zhang, Y.; Wang, S.; Xu, Honglei (COC Publications, 2012)
In this paper, we discuss a class of switched integro-differential control system with time delayin detection of switching signal, sufficient conditions are given to guarantee the system being asymptotically stable or exponentially stable.